2022
DOI: 10.1155/2022/5243825
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to Oral Medications and Low-Histamine Diet in Patients with Chronic Urticaria

Abstract: Background. Chronic urticaria (CU) is comprised of diverse phenotypes, and thus, a shift towards a precision medical approach is warranted in its management. Methods. This study enrolled 78 patients with CU. Serum erythrocyte sedimentation rate, hemoglobin, hematocrit, eosinophil count, IgE, antinuclear antibody (ANA), and serum diamine oxidase (DAO) levels of the patients were measured and were compared according to the patient’s response to second-generation antihistamines (sgAH), corticosteroids, leukotrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…At present, the low-histamine diet cannot be routinely recommended in hEDS/HSD despite its apparent efficacy (Figure 2a) for reasons including lack of evidence in DGBI and risks of disordered eating behaviors with elimination diets (35). A recent study demonstrated that deficiency of diamine oxidase, an enzyme that breaks down histamine, is a good biomarker for response to a low-histamine diet, in patients with chronic urticaria (36). Further research is required in patients with hEDS/HSD to investigate the efficacy of the low-histamine diet and whether diamine oxidase may be a good biomarker of its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the low-histamine diet cannot be routinely recommended in hEDS/HSD despite its apparent efficacy (Figure 2a) for reasons including lack of evidence in DGBI and risks of disordered eating behaviors with elimination diets (35). A recent study demonstrated that deficiency of diamine oxidase, an enzyme that breaks down histamine, is a good biomarker for response to a low-histamine diet, in patients with chronic urticaria (36). Further research is required in patients with hEDS/HSD to investigate the efficacy of the low-histamine diet and whether diamine oxidase may be a good biomarker of its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several promising biomarkers are under focus to predict the efficacy of dietary intervention for the treatment of CSU. 9 A study of 240 children with CSU has shown that food sensitization could predict inadequate treatment response. 10 There are limited references in the literature about IgG food testing in CSU.…”
Section: Discussionmentioning
confidence: 99%